Influence of fibers on bond strength of concrete exposed to elevated temperature - Varghese, Alwyn; Anand, N.; Arulraj, G. Prince; Alengaram, Ubagaram Johnson (Taylor & Francis, 2019)
Concrete is a building material having good fire resistance and the resistance depend on many factors including the properties of its constituent materials. Fiber Reinforced Concrete (FRC) apart from improving mechanical properties has better fire resistance than conventional concrete. Bond strength of concrete is one of the important properties to be considered by structural engineers while designing reinforced concrete cements. In this research, an experimental investigation has been carried out to determine the effect of fibers on the bond strength of different grades (M20, M30, M40 and M50) of concrete subjected to elevated temperature. Different types of fibers such as Aramid, Basalt, Carbon, Glass and Polypropylene were used in the concrete with a volume proportion of 0.25% to determine the bond strength by pull-out test. Prior to the pull-out test, the specimens were kept in a furnace and subjected to elevated temperatures following standard fire curve as per ISO 834. Based on the test results of the investigations, type of fiber, grade of concrete and duration of heating were found to be the key parameters that affect the bond strength of concrete. The contribution of carbon fiber in enhancing the bond strength was found to be more significant compared to other fibers. An empirical relationship has been developed to predict the bond strength of FRC at a slip of 0.25 mm. This empirical relationship is validated with experimental results. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.